Predictors of elevated C-reactive protein among pre-treatment, newly diagnosed breast cancer patients: a cross-sectional study - Abu Zaid, Zalina; Ng, Wai Han; Mohd Yusof, Barakatun Nisak; Amin Nordin, Syafinaz; Lim, Poh Ying (Elsevier Ltd, 2024)
Background & Aims: Accumulating evidence showed that inflammation contributes markedly to cancer progression, with C-reactive protein (CRP) being one of the lengthily studied inflammation marker. For breast cancer (BCa), pre-treatment elevated CRP upon diagnosis was linked with increased mortality. This study aimed to identify factors predictive of elevated CRP in pre-treatment BCa population that can serve as potential therapeutic targets to reduce inflammation.Methods: This is a cross-sectional study using multiple logistic regression to identify predictors of elevated CRP among pre-treatment, newly diagnosed BCa patients. Studied variables were socio-demographic and medical characteristics, anthropometric measurements [body weight, Body Mass Index, body fat percentage, fat mass/fat free mass ratio, muscle mass, visceral fat], biochemical parameters [albumin, hemoglobin, white blood cell (WBC), neutrophil, lymphocyte], energy-adjusted Dietary Inflammatory Index, handgrip strength (HGS), scored Patient Generated-Subjective Global Assessment, physical activity level and perceived stress scale (PSS). Results: A total of 105 participants took part in this study. Significant predictors of elevated CRP were body fat percentage (OR 1.222; 95 % CI 1.099–1.358; p < 0.001), PSS (OR 1.120; 95 % CI 1.026–1.223; p = 0.011), low vs normal HGS (OR 41.928; 95 % CI 2.155–815.728; p = 0.014), albumin (OR 0.779; 95 % CI 0.632–0.960; p = 0.019), and WBC (OR 1.418; 95% CI 1.024–1.963; p = 0.036). Conclusion: Overall, predictors of elevated CRP in pre-treatment, newly diagnosed BCa population were body fat percentage, PSS, HGS category, albumin and WBC.